Evaluation and improvement of the main insulation structure of 33kV distribution transformer based on FEM - Ibrahim Jalil Jebur; Kassim Rasheed Hameed (Institute of Advanced Engineering and Science, 2019)
This paper introduces a 2-D FE model to analyze the electric field distribution to evaluate and improve the insulation structure of the 250kVA, 33/0.4kV wound core type distribution transformer using the ANSYS 17.2 by implementing APDL program. The dielectric lighting impulse test was simulated in order to test the presented transformer model according to the IEC67006-3 standard, the assessment process is based on determining the electric stresses and compare it with the maximum permissible value of electric field intensity. Three proposed FE model as an improvement to the insulation structure of the transformer included reducing the insulation distances, changing the materials type, and mix both of them. The results obtained from the FE solution were compared with those of the real test, and presented in form of contours, curves, and vectors. The results obtained from the presented model can be further treated as a reference data in the design process.